Enhanced switching stability in Ta2O5 resistive RAM by fluorine doping - Yuzheng Guo (Applied Physics Letters, 2017)
The effect of fluorine doping on the switching stability of Ta2O5 resistive random access memory devices is investigated. It shows that the dopant serves to increase the memory window and improve the stability of the resistive states due to the neutralization of oxygen vacancies. The ability to alter the current in the low resistance state with set current compliance coupled with large memory window makes multilevel cell switching more favorable. The devices have set and reset voltages of <1 V with improved stability due to the fluorine doping. Density functional modeling shows that the incorporation of fluorine dopant atoms at the two-fold O vacancy site in the oxide network removes the defect state in the mid bandgap, lowering the overall density of defects capable of forming conductive filaments. This reduces the probability of forming alternative conducting paths and hence improves the current stability in the low resistance states. The doped devices exhibit more stable resistive states in both dc and pulsed set and reset cycles. The retention failure time is estimated to be a minimum of 2 years for F-doped devices measured by temperature accelerated and stress voltage accelerated retention failure methods.